2023
DOI: 10.3390/biomedicines11020448
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Genetic Mechanisms of COPD, Its Diagnosis, Treatment, and Relationship with Lung Cancer

Abstract: Chronic obstructive pulmonary disease (COPD) is one of the most prevalent chronic adult diseases, with significant worldwide morbidity and mortality. Although long-term tobacco smoking is a critical risk factor for this global health problem, its molecular mechanisms remain unclear. Several phenomena are thought to be involved in the evolution of emphysema, including airway inflammation, proteinase/anti-proteinase imbalance, oxidative stress, and genetic/epigenetic modifications. Furthermore, COPD is one main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 267 publications
1
3
0
Order By: Relevance
“…[ 133,134 ] COPD is a coronary lung disease normally observed in cigarette smokers. [ 135 ] This finding agrees with other studies that demonstrate a cigarette smoke has a similar health risk to incense smoke. Several studies have confirmed that households having a culture of daily incense burning have their residents at a 12% greater risk of cardiac disorders.…”
Section: Association Of Particulate Matters With Various Disorderssupporting
confidence: 92%
“…[ 133,134 ] COPD is a coronary lung disease normally observed in cigarette smokers. [ 135 ] This finding agrees with other studies that demonstrate a cigarette smoke has a similar health risk to incense smoke. Several studies have confirmed that households having a culture of daily incense burning have their residents at a 12% greater risk of cardiac disorders.…”
Section: Association Of Particulate Matters With Various Disorderssupporting
confidence: 92%
“…Epigenetic modifications, such as DNA methylation/demethylation and histone acetylation, can alter the gene expression patterns in both COPD and NSCLC [97]. Aberrant epigenetic marks can affect the function of genes involved in inflammation, cell cycle regulation, and DNA repair, among others.…”
Section: Other Predictive Biomarkers Evaluated In Nsclc Patients With...mentioning
confidence: 99%
“…The harmful substances present in cigarette smoke and air pollution (mainly particulate matter-PM 2.5), apart from directly damaging cells and tissues in the respiratory system, lead to an increased production of reactive oxygen species (ROS) and cause an oxidant-antioxidant imbalance. Smoking, additionally, decreases the effectiveness of antioxidants like glutathione peroxidase (GPx), which help neutralize ROS and maintain the balance between oxidants and antioxidants [37,38]. An increasing number of free radicals can harm critical metabolic pathways within bacteria-also those naturally present in that niche-weakening their ability to survive and thrive in the lung environment.…”
Section: Lung Microbiome Dysbiosismentioning
confidence: 99%